Definition of the marketing essence of the enterprise's competition policy - Pererva, Oleksandr Petrovych (Національна академія Національної гвардії України, 2024)
The report proves that in order to have a successful competitive policy, an enterprise must have clearly defined unique competitive advantages. These can be: high quality of products; innovation of technological processes; favorable prices due to cost optimization; reputation of a reliable supplier; speed of order fulfillment and flexibility in responding to market needs.
Keywords: competitiveness; market policy; marketing; program; essence; methodology; industrial enterprises